Mammary Fibroadenoma in American Staffordshire Terrier Dog: A Case Report - Wiratama, Arfin; Wira, Dwi Wahyudha; Santoso, Fransiskus Teguh; Ayu, Nurul Aeni; Utamie, Mustika Ayu; Hafidzah, Haya (Jurnal Veteriner; Vol 26 No 2 (2025)DO - 10.19087/jveteriner.2025.26.2.231, 2025)
Mammary tumors in dogs represent 50-70% of all neoplasms diagnosed in older female dogs. This article reports the case of a 13-year-old American Staffordshire dog presented in West Java Animal Hospital with palpable masses on its mammary gland that had been progressively enlarged over six months. Clinical examination revealed the presence of masses in the pars abdominalis caudalis  and pars inguinalis of the mammary glands bilaterally. Further examination was conducted through Fine Needle Aspiration Cytology (FNAC). Cytological examination revealed multiple prominent nucleoli that have variation in nuclei size and shape, and the presence of a benign cell tumor was identified. Blood tests were also performed to evaluate the dog's health status, yielding relatively normal results, although a decreased hematocrit (HCT) was observed as a potential indicator of overhydration. Based on clinical examination and diagnostic findings, the dog was diagnosed with mammary fibroadenoma with a good prognosis, indicating a high recovery rate potential. Treatment was carried out by mastectomy to remove the tumor in the mammary glands of the dog. Post-operative care included the administration of antibiotic, analgesic, and anti-inflammatory medications. The dog was brought back by its owner to the hospital after 14 days for post-operative consultation during which the surgical wound was found to be dry and healed. Post-operative results showed a significant improvement in the healing status of the clinical symptoms experienced.